Levels of personality traits to predict creative thinking and decision making styles - KALI SOYER, MAKBULE (My University, 2021)
The main purpose of this research is to determine the personality traits of university students predicted by decisionmaking styles and creative thinking skills at a meaningful level. Whether decision-making styles, personality traits and creative thinking skills show a significant difference according to gender is also the sub-objective of the study. 419 university students attending in different universities in Istanbul participated in the research. Personal information form, Rational and Intuitive Decision Making Scale, Marmara Creative Thinking Disposition Scale and Adjectives Based Personality Test were used as data collection tools. In the analysis of the data, independent t test, Pearson Moment correlation coefficients and multiple linear regression analysis were used. According to result female students think more intuitively than male students and rational thinking style does not differ according to gender. It has been found that men are more courageous and curious in terms of creative thinking. In terms of personality traits female students showed more personality traits of emotional instability, extraversion, openness to experience, and compliance than male students. It was concluded that openness to experience, from personality traits, is a significant predictor of rational and intuitive decision styles. Lastly it was found that personality traits of extraversion, openness to experience, and emotional instability are significant predictors of creative thinking.
Kişilik özelliklerinin karar verme stilleri ve yaratıcı düşünmeyi yordama düzeyleri